Journal of applied mathematics - Hindawi Publishing Corporation ([Cairo, Egypt] ; [Cuyahoga Falls, Ohio] : Hindawi Pub. Corp., 2001)
"[The] Journal of Applied Mathematics is a refereed journal devoted to the publication of original research papers and review articles in all areas of applied, computational, and industrial mathematics. Subject areas include (but are not limited to) approximation theory, computing, control and systems, differential equations and dynamical systems, financial mathematics, fluid mechanics and solid mechanics, fractional calculus and its applications, linear and nonlinear waves, numerical algorithms, numerical analysis, operations research, optimization, partial differential equations, probability and stochastic processes, simulation, statistics, wavelets and wavelet transforms"--Journal home page (Hindawi Web site, viewed Jan. 29, 2008).
Title from journal home page (Hindawi Web site, viewed May 7, 2003).
Published: [Cairo, Egypt ; New York, NY], 2003-
Issues for 2003- have year as volume no.; articles continuously posted as they are accepted for publication.
Mode of access: World Wide Web.
Vol. 2007 (Hindawi Web site, viewed Jan. 29, 2008).
Keywords: Engineering mathematics -- Periodicals; Electronics -- Mathematics -- Periodicals; Industrial engineering -- Mathematics -- Periodicals; Mathematics -- Periodicals; Mathématiques de l'ingénieur.; Électronique -- Mathématiques.; Génie industriel; Mathématiques.; Applied Mathematics; Electronics -- Mathematics; Engineering mathematics; Industrial engineering -- Mathematics; Mathematics; Electronic journals